2013
DOI: 10.1016/j.jeem.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Preference elicitation under oath

Abstract: Eliciting sincere preferences for non-market goods remains a challenge due to the discrepency between hypothetical and real behavior and false zeros. The gap arises because people either overstate hypothetical values or understate real commitments or a combination of both. Herein we examine whether the traditional real-world institution of the solemn oath can improve preference elicitation. Applying the social psychology theory on the oath as a truth-telling-commitment device, we ask our bidders to swear on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(44 citation statements)
references
References 48 publications
(44 reference statements)
1
41
2
Order By: Relevance
“…This argument is based on evidence from social psychology that tests the effect of making a promise (Albarracín et al ; Durantini et al ; Girandola and Bernard ). Recent studies have investigated the effect of an oath script in environmental studies (Carlsson et al ; Jacquemet et al , , ) and food surveys (de‐Magistris and Pascucci ). Jacquemet et al () suggest that under oath, bidders seem to take both the budget constraint and participation constraint more seriously than with a cheap‐talk script.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This argument is based on evidence from social psychology that tests the effect of making a promise (Albarracín et al ; Durantini et al ; Girandola and Bernard ). Recent studies have investigated the effect of an oath script in environmental studies (Carlsson et al ; Jacquemet et al , , ) and food surveys (de‐Magistris and Pascucci ). Jacquemet et al () suggest that under oath, bidders seem to take both the budget constraint and participation constraint more seriously than with a cheap‐talk script.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have assessed the effects of combining and comparing various techniques to reduce hypothetical bias. Jacquemet et al () evaluated the effect of cheap talk and oath and concluded that the two are complementary—cheap talk overcomes a bidder's lack of experience with the good, which makes some people think that they are telling the truth when in actuality they are not. But it is the oath, not cheap‐talk scripts, that increases the odds of truth‐telling.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Specific approaches include the use of (1) certainty scales as in Champ et al, (1997), (2) entreaties to behave as if the decisions were real as in the “cheap-talk” protocol of Cummings and Taylor, 1999, or more recently the “solemn oath” protocol of Jacquemet et al, 2012), and (3) “dissonance-minimizing” protocols (as in Blamey et al, 1999, and Loomis et al, 1999, which allow respondents to express support for a public good while also indicating a low WTP). …”
mentioning
confidence: 99%
“…Do you understand what I am talking about? We want you to behave, in the Jacquemet et al (2009Jacquemet et al ( , 2013. In fact, before responding to the CV questions, each respondent was first asked to sign a truth-telling oath.…”
Section: Treatmentsmentioning
confidence: 99%
“…Given the non-conclusive results on the effectiveness of the CT in mitigating vhypothetical bias, Jacquemet et al (2011Jacquemet et al ( , 2013 proposed the use of another ex-ante non-monetary correction technique taken from the social psychology and called the "solemn oath". They argued that the solemn oath can be used as a truthtelling commitment device, by asking the bidders to swear on their honor to give honest answers prior to participating in a non-hypothetical experimental setting (i.e.…”
mentioning
confidence: 99%